Long-term outcomes of induction chemotherapy followed by chemoradiotherapy using volumetric-modulated arc therapy as an organ preservation approach in patients with stage IVA-B oropharyngeal or hypopharyngeal cancers. (17th June 2020) - Kubo, Katsumaro; Murakami, Yuji; Kenjo, Masahiro; Imano, Nobuki; Takeuchi, Yuki; Nishibuchi, Ikuno; Kimura, Tomoki; Kawahara, Daisuke; Ueda, Tsutomu; Takeno, Sachio; Nagata, Yasushi
Abstract: The present study aimed to analyze treatment outcomes after induction chemotherapy followed by chemoradiotherapy (CRT) using volumetric-modulated arc therapy (VMAT) in patients with stage IVA-B oropharyngeal cancer (OPC) or hypopharyngeal cancer (HPC), with long-term observation, including examination of larynx preservation. A total of 60 patients with stage IVA-B OPC or HPC, who underwent induction TPF chemotherapy (a combination regimen consisting of docetaxel, cisplatin, and 5-fluorouracil) followed by CRT using VMAT were analyzed. Overall survival (OS), progression-free survival (PFS), laryngoesophageal dysfunction-free survival (LEDFS), and locoregional control (LRC) were calculated and compared. Univariate and multivariate analyses were performed to determine statistical differences in OS and LEDFS. The median follow-up period at the time of evaluation was 61 months. Twenty-six (43%) patients had OPC and 34 (57%) had HPC. The 5-year OS, PFS, LEDFS, and LRC rates were 57%, 52%, 52%, and 68%, respectively. Response to TPF therapy was the only significant predictive factor of OS and LEDFS in multivariate analyses. Regarding long-term toxicities, grade ≥ 2 late toxicities accounted for 15%. No patients experienced grade ≥ 3 xerostomia, and 5% of all patients developed grade 3 dysphagia. With long-term observation, the OS, PFS, and LEDFS rates were relatively good, and the incidence of late toxicities was low. TPF followed by CRT using VMAT was feasible and more effective in those who responded to induction chemotherapy.